Patients’ Privacy in the Operating Room: Perspectives from Patients in Academic Hospitals of Guilan (Iran) - Hossein Khoshrang; Abbas Sedighinejad; Morteza R. Taramsari; Niloofar Azizinezhad; Mandana Javanak; Mohadese Ahmadi; Gelareh Biazar (Iranian Journal of Nursing and Midwifery Research)
Background: Privacy, recognized as a fundamental patient right, has become a focal point within the healthcare system. This study was conducted to evaluate the state of patients’ privacy in the operating rooms of academic hospitals affiliated with Guilan University of Medical Sciences in Iran. Materials and Methods: This cross-sectional descriptive study was carried out between October 2022 and April 2023. Eligible patients completed a questionnaire that included four sections: demographic information and physical, informational, and social dimensions of patient privacy. Results: Data from 215 patients were analyzed. Younger (Mann–Whitney U = 4738, Z = −2.44, p = 0.01) and single (Chi_square 7.62, p = 0.02) patients significantly achieved higher scores. Male (Mann–Whitney U = 4918.5, Z = −0.90, p = 0.36) and rural (Mann–Whitney U = 5411, Z = −0.43, p = 0.66) patients also had higher scores; however, the differences were not significant. Comparing results across the five participating centers in three distinct dimensions, a significant variation was observed in the physical dimension (Chi_square = 22.76, p < 0.0001). However, no significant differences were noted in the informational (Chi_square = 9.11, p = 0.05) and social dimensions (Chi_square = 8.78, p = 0.06). Among hospital sectors, the Ophthalmic and ENT surgeries units’ mean (SD) scored the highest 14 (1.53), closely followed by the obstetrics’ mean (SD) 13.88 (1.98), while the cardiac surgery center’s mean (SD) scored the lowest 12.3 (2.53). Conclusions: Patients’ privacy was upheld, but there remains room for improvement by ensuring sufficient perioperative information is provided for the patients. Additional attention should be directed toward elderly patients and those with a history of divorce.